Hermenêutica tradutória como receptividade crítica - Dutra, Gabriel Lins e Silva (2025)
The subject of this research is contemporary Translational Hermeneutics. It is forwarded from a bifold point of view, a portrayal in contrast with other theoretical approaches to the research field, and an immanent description of the historical-conceptual development of the hermeneutical tradition in Western philosophy. This master’s dissertation is a literature review of exploratory nature. The methodology applied here was based mainly on Porta (2007), but also on Marconi & Lakatos (2003) and Gil (2002). Our question aims at the previous knowledge required for an adequate understanding of the approach. As an answer to this question, this dissertation raised the hypothesis that such contribution can be structured departing from Radegundis Stolze’s Hermeneutik und Translation. Translational Hermeneutics can lead to research possibilities that go beyond particular limitations faced by the various methodologies and approaches to this field of research (Stolze, 2003: 14-37, 104). After making introductory remarks on the subject, methodological considerations are forwarded so as to make the theoretical framework of this research known. The first thematic focus introduces Translational Hermeneutics’ position in relation to other approaches. The second presents the historical and philosophical background of Hermeneutics. The third and final one shows how some key ideas from Hermeneutics are relevant in the sense of offering a theoretical model which is representative of the attitude of receptivity the translator should have in relation to the communicative event of the text, especially in sight of some important topics in translation and language research.